Pilot study on a new endoscopic platform for colorectal endoscopic submucosal dissection - Maselli, Roberta; Spadaccini, Marco; Galtieri, Piera Alessia; Badalamenti, Matteo; Ferrara, Elisa Chiara; Pellegatta, Gaia; Capogreco, Antonio; Carrara, Silvia; Anderloni, Andrea; Fugazza, Alessandro; Hassan, Cesare; Repici, Alessandro (Therapeutic advances in gastroenterology, 2023)
Background: The endoscopic submucosal dissection (ESD) is a technically demanding and time-consuming procedure, with an increased risk of adverse events compared to standard endoscopic resection techniques. The main difficulties are related to the instability of the operating field and to the loss of traction. We aimed to evaluate in a pilot trial a new endoscopic platform [tissue retractor system (TRS); ORISE, Boston scientific Co., Marlborough, MA, USA], designed to stabilize the intraluminal space, and to provide tissue retraction and counter traction. Method: We prospectively enrolled all consecutive patients who underwent an ESD for sigmoid/rectal lesions. The primary outcome was the rate of technical feasibility. Further technical aspects such as en-bloc and R0 resection rate, number of graspers used, circumferential incision time, TRS assemblage time, submucosal dissection time, and submucosal dissection speed were provided. Clinical outcomes (recurrence rate and adverse events) were recorded as well. Results: In all, 10 patients (M/F 4/6, age: 70.4 ± 11.0 years old) were enrolled. Eight out of 10 lesions were located in the rectum. Average lesion size was 31.2 ± 2.7 mm, and mean lesion area was 1628.88 ± 205.3 mm2. The two sigmoid lesions were removed through standard ESD, because the platform assemblage failed after several attempts. All rectal lesions were removed in an en-bloc fashion. R0 resection was achieved in 7/8 (87.5%) patients in an average procedure time of 60.5 ± 23.3 min. None of the patients developed neither intraprocedural nor postprocedural adverse events. Conclusion: TRS-assisted ESD is a feasible option when used in the rectum, with promising result in terms of efficacy and safety outcomes. Nevertheless, our pilot study underlines few technical limitations of the present platform that need to be overcome before the system could be widely and routinely used.